Service personnel for the maintenance, thorough examination, operational testing, overhaul and repair of lifeboats (including free-fall lifeboats) and rescue boats (including fast rescue boats), launching appliances and release gear. Level 2 in-field competence Part 4, (6th March 2020) - British Standards Institution,
No abstract available